Persuasion vs evasion: strategies in political interview - N. V. Stepanova (Дискурс)
Introduction. Introduction explores the political interview genre, which is an efficient way of affecting the audience as well as a tool of forming public opinion. Key strategies of political interview namely persuasive and evasive ones are given. Basic tactics helping in carrying out these strategies in political interview are outlined.Materials and methods. Materials and methods are explored in a corresponding paragraph of the paper. D. Trump, H. Clinton and E. Macron interviews transcripts in the English language are used as material for the research. Transcripts are studied within the frame of conceptual integration theory (cognitive metaphor and mental spaces study) and discourse analysis (linguistic and extra linguistic discourse features investigation).Results. Results of the research represent specific examples of studying persuasive and evasive strategies revealing corresponding tactics while drawing conceptual integration schemes (for persuasive strategy) and examining particular phrases from the interview taking into account political and social context (for evasive strategy).Discussion. Discussion is devoted to summarizing the investigation and reviewing the results. Among the persuasive tactics Ettiketirung and discreditation tactics prevail in the material studied. The most popular evasive tactics are mitigation, generalization, compliance with the journalist, admission of guilt. Cognitive metaphor is an effective way of implementing persuasive strategy while it is used rarely in carrying out evasive strategy. As far as psychological image of the politicians is concerned, H. Clinton and D. Trump tend to be using persuasive strategy, whereas E. Macron prefers to be evasive. Also, the French President often implements stable emotional state strategy.Conclusion. Conclusion contemplates the outlook of the research given. Further studying of persuasive, evasive and other discursive strategies is planned based on political interviews and political discourse in general.